Probiotics as prevention for gastro-intestinal disorders in pediatrics - Yvan Vandenplas (Indonesian Nutrition Association, 2020)
This is a narrative review of largely randomized trials on the impacts of probiotics. It concludes that evidence for beneficial effects of selected probiotics in the prevention of gastrointestinal disorders is limited mainly to acute gastroenteritis, antibiotic-associated diarrhea, infantile colic and necrotizing enterocolitis.Â However, there is no broad consensus to recommend the use of probiotics in the prevention of these conditions, mainly because of the different designs used in different studies, resulting in limited evidence for specific strains, dosages and indications. More well-designed studies utilizing standardized methodologies are needed before recommendations can be proposed. At this stage, there is insufficient evidence to recommend the routine use of probiotics in infants and children for the prevention of gastro-intestinal disorders